Wear contact problem with friction: Steady-state regime and wearing-in period. (1st June 2020) - Argatov, I.I.; Chai, Y.S.
Abstract: A two-dimensional contact problem for an elastic layer of a finite thickness is considered with the effects of friction and wear taken into account. It is assumed that the contact zone is constant, but the shape of a wear-resisting punch changes during the sliding wear process. The punch is loaded by constant external normal and tangential loads, the latter of which is equal to the maximum value predicted by Coulomb's law. The steady-state profile of the punch, which has been reproduced in the steady-state wear regime, is determined in an integral form. In the case of a very thick layer, explicit formulas are given for the initial vertical displacement of the punch and the moment of contact pressures, both of which vary during the wear process. The duration of the wearing-in process is estimated, and it is shown that the effect of friction extends the wearing-in period.